Penerapan Model Pembelajaran Kooperatif Tipe Student Team Achievement Division Untuk Meningkatkan Aktivitas dan Hasil Belajar Siswa di Kelas IV SDN Kawatuna - Nasmin Baso Ali; I Komang Werdhiana; Hartono D. Mamu (Mitra Sains, 2016)
The problem in this study was the lack of student activities and low learning outcomes of students in science subject at fourth grade SDN Kawatuna Palu. This study was classroom action research consist of two cycles. Each cycle consists of two meetings. The stages of every cycle were planning, action, observation and reflection. By through the six phases of Student Team Achievement Division (STAD) learning, that students activity and student learning outcomes on the material force and motion of objects might increase. The activity of student in first cycle reached 72.7%, (good categories according to Likert scale), teacher activity reached 75% (good categories) and learning outcomes in the form of classical completeness reached 59.4% (enough category). In the second cycle, the student activity reached 84.9% and teacher reached 87.5%, the result of classical completeness increased up to 100%. These results provide a positive impact in improving the activity and student learning outcomes. STAD might made students more familiar and more active in learning. Familiar means that students work together in completing the LKS group, they cooperate by accepting the differences of each member of the group. Active in this case was students more active to ask and answer the question, both of teachers and of other groups at the time of the learning process.